Classical philology and linguistics : old themes and new perspectives - Giannakīs, Geōrgios K.; Filos, Panagiotis, 1972-; Crespo, Emilio, 1950-; Villa, Jesús de la (Trends in Classics. Greek and Latin linguistics ;, 2023)
There is a long-standing debate over the relation of historical linguistics and classical philology, especially within the purview of the renewed interest in it during the last decades and the recent trends that characterize philological and linguistic studies. Ever since its appearance in the nineteenth century, the history of this debate testifies to a turbulent coexistence and fertile collaboration of the two disciplines, but at times also moving along centrifugal paths. The essays in this volume address this debate and cover various aspects of linguistic and philological research of Greek and Latin, moving in the middle ground where language, linguistics and philology crosscut and cross-fertilize each other highlighting the application of linguistic theory to the study of classical texts and drawing on fields such as syntactic theory and pragmatics, historical semantics and the lexicon, reconstruction and etymology, dialectology, editorial practices, the use of corpora, and other interdisciplinary approaches that function as hinges between philology and linguistics.